2020
DOI: 10.1007/s10701-020-00363-3
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Interpretation of Correspondence Principle: Solution of Nodal Issue

Abstract: The correspondence principle states that the quantum system will approach to the classical system in high quantum numbers. Indeed, the average of the probability density distribution reflects a classicallike distribution. However, the likelihood of finding a particle at node of the wave function is zero. This condition is recognized as the nodal issue. In this paper, we propose a solution for this issue by means of complex quantum random trajectories which are obtained by solving the stochastic differential eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…As is well-known, there are nodes with in the quantum harmonic oscillator. In our previous work [ 42 ], we solved this so-called nodal issue in the framework of complex mechanics. The statistical method we used was to collect all points of the CQRTs with the same real part : …”
Section: Extending Probability To the Complex Planementioning
confidence: 99%
See 1 more Smart Citation
“…As is well-known, there are nodes with in the quantum harmonic oscillator. In our previous work [ 42 ], we solved this so-called nodal issue in the framework of complex mechanics. The statistical method we used was to collect all points of the CQRTs with the same real part : …”
Section: Extending Probability To the Complex Planementioning
confidence: 99%
“… The statistical distribution of an ensemble of intersection points and projection points on the real axis of the CQRTs for state. The red solid line is the quantum probability distribution and the black dotted line is the statistical distribution of point set B [ 42 ]. …”
Section: Figurementioning
confidence: 99%
“…As is well-known, there are nodes with 𝛹(𝑥) = 0 in the quantum harmonic oscillator. In our previous work [42], we solved this so-called nodal issue in the framework of complex mechanics. The statistical method we used was to collect all points of the CQRTs with the same real part 𝑥:…”
Section: Extending Probability To the Complex Planementioning
confidence: 99%
“…It is established on the foundation of the complex-space structure within which all physics quantities are complex-valued [51]. The quantum operators, quantization rules, uncertainty principle, correspondence principle, quantum probability, spin, and all other fundamental properties of quantum mechanics can have their corresponding trajectory-based descriptions underlying the framework of QHM in the complex domain [52][53][54][55]. It was found that the spin motion of the electron in the hydrogen atom is independent of the wave function, and is determined solely by the geometrical property of the complex-space structure [56,57].…”
Section: Introductionmentioning
confidence: 99%